2019
DOI: 10.1111/polp.12329
|View full text |Cite
|
Sign up to set email alerts
|

You Are Who You Think You Are: Linked Fate and Vote Choices among Latino Voters

Abstract: Analysts of American politics have long considered the growing power of the Latino population in the United States as a significant variable for elections. However, the assumption that Latinos will share similar political views and behaviors is, at best, unsettled with mixed results from existing studies. In this research, we use original data to test whether Latino voters are more likely to act based on the view that their individual fates are connected with those of their racial or ethnic group, or are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…By 2006, the Latino National Political Survey also found that a large majority of Latinos identified with the pan‐ethnic term (Barreto and Segura 2014). The importance of not studying an entire ethnicity as a monolith has been seen through the contrasting results in elections and party affiliations, most notably the comparison between Florida Latinos and Latinos elsewhere (Escaleras, Kim, and Wagner 2019; Yang and de la Garza 2017).…”
Section: Latinos and Equal Opportunity Policiesmentioning
confidence: 99%
See 4 more Smart Citations
“…By 2006, the Latino National Political Survey also found that a large majority of Latinos identified with the pan‐ethnic term (Barreto and Segura 2014). The importance of not studying an entire ethnicity as a monolith has been seen through the contrasting results in elections and party affiliations, most notably the comparison between Florida Latinos and Latinos elsewhere (Escaleras, Kim, and Wagner 2019; Yang and de la Garza 2017).…”
Section: Latinos and Equal Opportunity Policiesmentioning
confidence: 99%
“…While the connections between group positions on policy issues, linked fate, and voting behavior have been studied extensively for Blacks and Whites, similar evidence for Latinos has been mixed. For one, Latinos are generally not thought to be attached as close to their group label as other groups (Bishin, Kaufmann, and Stevens 2012;Escaleras, Kim, and Wagner 2019;Gutierrez et al 2019). There has, however, been some research suggesting that the increasing attention to the Latino electorate and the grouping of ethnic groups generally considered to be "Latino" by outsiders has built a larger and more cohesive group that could produce a "Latino vote" (Barreto and Segura 2014;Escaleras, Kim, and Wagner 2019).…”
mentioning
confidence: 99%
See 3 more Smart Citations